Feasibility Analysis Of Class Vi Students 'Books in Globalization Theme (Theme 4) Curriculum 2013 SDN 2 Padasuka - Nurjamaludin, Muhammad; Aprilia, Nabila; Gunawan, Dani; Muslihah, Neni Nadhiroti (Universitas Sebelas Maret, 2021)
Textbooks are one of the teaching materials that can influence in learning activities, because they can be a reference for teachers and students. The purpose of this study was to determine the four standard feasibility of a grade VI student book on the theme of globalization in the curriculum 2013. The research method used in this study is qualitative with a type of descriptive approach that is library research. Participants or research objects that act as a source of data research information are the books of grade VI students and teachers. The data collection techniques used are documentation and interview techniques. Based on the results of the research analysis, it shows that the average value of the standardized analysis of the grade student book on the theme of globalization obtained a percentage 85,31% with the title “very worthy”. Thus this book can be used as best as possible.